PEMANFAATAN ANALISIS DATA MEDIA SOSIAL UNTUK MENINGKATKAN KINERJA PEMASARAN - Mirwansyah Putra Ritonga; Komala Dewi (ADISAM PUBLISHER, 2025)
The utilisation of social media data analytics has become a key element in improving marketing performance in the digital age. Accurate and detailed data analysis allows companies to deeply understand the behaviour, preferences and needs of their audience. With this information, companies can design more effective marketing strategies, personalise campaigns, and improve interactions with customers. The implementation of strategies powered by social media data requires a combination of automation technology, collaboration between teams, and continuous optimisation. Successfully utilising this data analysis not only improves the effectiveness of marketing campaigns but also strengthens the company's competitive position and supports long- term business growth